Sintilimab and anlotinib with gemcitabine plus cisplatin in advanced biliary tract cancer: SAGC a randomized phase 2 trial - Jingjing Li; Shurui Zhou; Xiaoqing Xu; Qinhong Zheng; Fabiao Zhang; Cong Luo; Da Li; Xing Sun; Zhe Han; Wei Wu; Junrong Yan; Yang Shao; et al. (Nature Communications)
Abstract Biliary tract cancer (BTC) has a poor prognosis with limited treatment options. This phase 2 trial randomized 80 patients with unresectable/metastatic BTC 1:1 to sintilimab, anlotinib, and gemcitabine/cisplatin (SAGC) or chemotherapy alone (GC). At 13.4-month median follow-up, SAGC significantly improved median progression-free survival (8.5 vs. 6.3 months; HR 0.48, 95% CI 0.22–0.64, p = 0.005) and objective response rate (51.4% vs. 29.4%), with higher grade 3/4 adverse events (75.0% vs. 43.6%). Post hoc analysis showed enhanced efficacy with anlotinib 8 mg versus 10 mg (ORR 54.5% vs. 38.8%). In AKT/YAP tumor models, low-dose anlotinib (3 mg/kg) combined with sintilimab improved vascular perfusion, T-cell cytotoxicity, and cytokine secretion compared to high-dose (6 mg/kg). These findings demonstrate improved efficacy and manageable toxicity with SAGC, particularly at the 8 mg anlotinib dose, suggesting low-dose regimens may optimize antitumor response while mitigating adverse effects. Trial registration number ClinicalTrials.gov Identifier: NCT04300959.